Interpretación de la curación periapical en imágenes radiológicas. Una revisión - Archila-Montañez, Eloísa (2021)
Interpretation of the state of healing of chronic apical periodontitis or apical curettage with apicoectomy in radiological images is based on the analysis of changes in the appearance of the periapical area and in the bone structure adjacent to the site of inflammation or surgical intervention, which are projected onto normal bone structures. However, distortion of structures or the superposition of anatomical images should be considered when interpreting radiographs. We compared conventional studies of evaluation of the periapical area following treatment, together with 2D images, with the periapical index and the criteria of evaluation in both successful and unsuccessful cases of endodontic surgical treatment. Some studies have reported that the radiographic appearance of the tooth crown and root may facilitate interpretation of the periapical area. In addition, cone-beam computed tomography can show the relationship between injured and repairing tissue using buccal and lingual tables to measure the periphery in transverse reconstruction. Indeed, complex biological events and mechanisms can occur during the healing process of periapical and root tissues. Knowledge of the diversity of tissues is essential to identify the dynamics of the signs of regeneration or the presence of healing due to repair. Hence, the aim of this article was to identify the criteria used to interpret periapical healing in two-dimensional or three-dimensional images and their relationship with diagnosis and treatment according to the literature currently available.